An Introduction to the Theory of Numbers - Moser, Leo; Open Textbook Library (Open Textbook Library, 2011)
This book, which presupposes familiarity only with the most elementary concepts of arithmetic (divisibility properties, greatest common divisor, etc.), is an expanded version of a series of lectures for graduate students on elementary number theory. Topics include: Compositions and Partitions; Arithmetic Functions; Distribution of Primes; Irrational Numbers; Congruences; Diophantine Equations; Combinatorial Number Theory; and Geometry of Numbers. Three sections of problems (which include exercises as well as unsolved problems) complete the text.
Chapter 1. Compositions and Partitions -- Chapter 2. Arithmetic Functions -- Chapter 3. Distribution of Primes -- Chapter 4. Irrational Numbers -- Chapter 5. Congruences -- Chapter 6. Diophantine Equations -- Chapter 7. Combinatorial Number Theory -- Chapter 8. Geometry of Numbers
In English.
Description based on online resource
Keywords: Mathematics -- Textbooks